Adult intussusception secondary to diverticular disease. (8th November 2018) - Syed, Habib; Syed, Labib; Parampalli, Umesh; Uheba, Mokhtar
Abstract : Intussusception is the invagination of a proximal segment of bowel into the lumen of an adjacent distal segment. It is a common condition in the paediatric age group although it rarely occurs in adults. Organic lesions in the bowel wall are the primary cause of adult intussusceptions with malignant neoplasms being the most common. However, we present a rare case of a 92-year-old man diagnosed with an intussusception of the sigmoid-rectal colon secondary to a diverticular stricture.